GAMBARAN FAKTOR RESIKO KEJANG DEMAM BERULANG PADA ANAK DI RSUD DR. PIRNGADI MEDAN TAHUN 2016 - 2020 - SISCA SILVANA; REGIS JUANG OIMOLALA WARUWU (JURNAL ILMIAH SIMANTEK, 2022)
This type of research is a retrospective descriptive study with a cross sectional study design on 86 children with recurrentfebrile seizures at RSUD Dr. Pirngadi, Medan which was selected using total sampling using medical record data (secondarydata), in December 2021. Then the data were analyzed using a descriptive method and arranged in a distribution table.From the results of the study, it can be seen that children with recurrent febrile seizures mostly occurred in children with malesex, namely 51 people (59.3%). Children with recurrent febrile seizures experienced the most of children aged 1 year at thetime of the first febrile seizure, as many as 46 people (53.5%). Children with recurrent febrile seizures experienced the mostof children with a temperature of 390C during the first febrile seizure, as many as 78 people (90.7%). Children with recurrentfebrile seizures were most experienced by children with a time interval between fever and seizure <24 hours in the firstfebrile seizure, as many as 46 people (53.5%). Most children with recurrent febrile seizures experienced the type of simplefebrile seizure in the first febrile seizure, namely 51 people (59.3%). Children with recurrent febrile seizures were mostexperienced by children without a history of febrile seizures in the family, amounting to 80 people (93%). Children withrecurrent febrile seizures without a family history of epilepsy were 86 people (100.0%). The risk factors for recurrent febrileseizures were age 1 year, temperature 390C at the time of the first febrile seizure, male gender, time interval between feverand seizure <24 hours, complex type of febrile seizure, children with a family history of febrile seizures.